Structured model and parameter estimation in plant cell cultures of Thevetia peruviana (2023)
In this work, a mechanistic model for predicting the dynamic behavior of extracellular and intracellular nutrients, biomass production, and the main metabolites involved in the central carbon metabolism in plant cell cultures of Thevetia peruviana is pres